Myxozoan polar tubules display structural and functional variation. Issue 1 (December 2016) - Ben-David, Jonathan; Atkinson, Stephen; Pollak, Yulia; Yossifon, Gilad; Shavit, Uri; Bartholomew, Jerri; Lotan, Tamar
Abstract Background Myxozoa is a speciose group of endoparasitic cnidarians that can cause severe ecological and economic effects. Although highly reduced compared to free-living cnidarians, myxozoans have retained the phylum-defining stinging organelles, known as cnidae or polar capsules, which are essential to initiating host infection. To explore the adaptations of myxozoan polar capsules, we compared the structure, firing process and content release mechanism of polar tubules in myxospores of threeMyxobolus species includingM. cerebralis, the causative agent of whirling disease. Results We found novel functions and morphologies in myxozoan polar tubules. High-speed video analysis of the firing process of capsules from the threeMyxobolus species showed that all polar tubules rapidly extended and then contracted, an elasticity phenomenon that is unknown in free-living cnidarians. Interestingly, the duration of the tubule release differed among the three species by more than two orders of magnitude, ranging from 0.35 to 10 s. By dye-labeling the polar capsules prior to firing, we discovered that two of the species could release their entire capsule content, a delivery process not previously known from myxozoans. Having the role of content delivery and not simply anchoring suggests that cytotoxic or proteolytic compounds may be present in the capsule. Moreover, while free-living cnidarians inject most of the toxic content through the distal tip of the tubule, our video and ultrastructure analyses of the myxozoan tubules revealed patterns of double spirals of nodules and pores along parts of the tubules, and showed that the distal tip of the tubules was sealed. This helical pattern and distribution of openings may minimize the tubule mechanical weakness and improve resistance to the stress impose by firing. The finding that myxozoan tubule characteristics are very different from those of free-living cnidarians is suggestive of their adaptation to parasitic life. Conclusions These findings show that myxozoan polar tubules have more functions than previously assumed, and provide insight into their evolution from free-living ancestors.